Synergized regulation of NK cell education by NKG2A and specific Ly49 family members - Xiaoqian Zhang (Nature Portfolio, 2019)
MHC-I-induced signalling of various natural killer (NK) inhibitory receptors is critical for regulation NK cell education, but clear genetic evidence is still lacking. Here the authors generate multiple lines of mice differentially deficient in Ly49 family and/or NKG2A NK receptors, and find that self-MHCI specific Ly49 members and NKG2A synergize to regulate NK education.